Teaching of Mapuzugun in Chile: Echo-sonority as preparation for the acquisition of the indigenous language - Rivas Rivas, María Clara (2023)
This research study focuses on the process of acquiring the indigenous Mapuce language for teaching purposes in order to contribute to current Mapuzugun Indigenous Language programs. Using a dialogic participatory methodology called Kishu Kimkelay Ta Che, we collaborated with teachers and members of the Mapuce community from a rural school in La Araucanía, Chile. Our findings reveal that echo-sonority plays a crucial role in preparing for the teaching of the indigenous language. This preparation involves the relationship between sound-action, onomatopoeia-toponymy, and nature-language. We argue that these results present a necessary challenge to improve indigenous language programs, which mostly operate under a Western logic, making intercultural articulation in schools challenging.